2011
DOI: 10.1136/sextrans-2011-050132
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of HIV in Scotland, 1988–2009

Abstract: The reduction in the incidence rate among IDUs suggests that harm reduction measures initiated from the late 1980s were effective in reducing HIV transmission in this risk group; however, the absence of a reduction in HIV incidence rates among MSM is disappointing and highlights the need for renewed efforts in the prevention of HIV in this major risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In a recently published modelling study using data on MSM in England and Wales over the ten year period 2001 to 2010, there was no decrease in incidence despite an increase in HIV testing rates and high treatment coverage [10]. This study is not designed to measure incidence due to a number of limitations in its design; even a crude measure, using the self-reported HIV testing interval which is not reported by all study participants, estimates a level higher than that described in the Scottish study by McDonald et al which utilised locally collected testing data applicable to this population [6]. Notwithstanding the need for measuring incidence in this population, these results, along with the previous study results, provide valuable insights into the HIV testing and infection status of our MSM population over time.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a recently published modelling study using data on MSM in England and Wales over the ten year period 2001 to 2010, there was no decrease in incidence despite an increase in HIV testing rates and high treatment coverage [10]. This study is not designed to measure incidence due to a number of limitations in its design; even a crude measure, using the self-reported HIV testing interval which is not reported by all study participants, estimates a level higher than that described in the Scottish study by McDonald et al which utilised locally collected testing data applicable to this population [6]. Notwithstanding the need for measuring incidence in this population, these results, along with the previous study results, provide valuable insights into the HIV testing and infection status of our MSM population over time.…”
Section: Discussionmentioning
confidence: 88%
“…A study in Scotland among those undergoing repeat HIV testing estimated HIV incidence among MSM (15 per 1000 person years) was three to four fold higher than other populations at risk of, and tested for, HIV: this has remained unchanged since the late 1980s [6]. Recent data suggest that one in five HIV infected MSM remain undiagnosed and it is estimated that this population accounts for around half of all new HIV transmissions [1], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…The analyses build on early results published by Frischer and Goldberg (1997) as part of a WHO collaborative study, in which significantly higher mortality rates were observed in Glasgow compared to other centres despite the low prevalence of HIV. This follow-up study spanned a 30-year period over which changes in drug policy resulted in the rollout and expansion of needle and syringe programs, opioid substitution therapy, HIV and Hepatitis C testing and treatment and other harm reduction strategies (Aspinall et al, 2012;McDonald et al, 2012). Despite these and the utilisation of in-patient treatment services at cohort entry, significantly elevated mortality rates were observed up to three decades later.…”
Section: Discussionmentioning
confidence: 98%
“…Further, few have examined the impact of treatment access, such as age at treatment, on subsequent drug-related mortality. Frischer and Goldberg (1997) described the mortality of a cohort of PWID at a time when prevalence of HIV among PWID in Glasgow was low (2-4%) while the prevalence of Hepatitis C was high (approximately 70%) (McDonald et al, 2012;Taylor et al, 2000). In this context it is not surprising that 11% of the cohort who died, died largely as a result of drug-related causes rather than HIV-related causes.…”
Section: Introductionmentioning
confidence: 94%
“…This month, McDonald et al 3 report trends in Scotland, demonstrating a marked reduction in incidence among intravenous drug users yet stable and high incidence in MSM. HIV testing is one of the keys to effective prevention for MSM.…”
mentioning
confidence: 99%